Genomic and Immunoinformatics Insights Into a Bovine-Derived Brucella abortus S19 Field Strain: Adaptations Impacting Vaccine Efficacy - Arslan, Ali; Aktas, Emre; Sezerman, Osman Ugur; Ozbek, Tulin (WILEY, 2025)
Brucella abortus S19 is a widely used live attenuated vaccine strain for bovine brucellosis control; however, its long-term efficacy is challenged by genomic plasticity and adaptive mechanisms. This study presents a comprehensive comparative genomic and immunoinformatics analysis of a field strain (B. abortus S19, BAS19) isolated from an aborted cattle placenta 3 years post-vaccination in Erzurum, Turkey. Whole-genome sequencing was performed using Oxford Nanopore Technology, followed by genome assembly, functional annotation and comparative analyses against the reference strain (B. abortus S19, BAR19). Genomic variations, including 1153 single nucleotide polymorphisms (SNPs), 120 insertions and 2501 deletions, were identified. Annotation revealed 772 hypothetical proteins in BAS19 compared to 604 in BAR19, with distinct differences in virulence-associated genes. Immunoinformatics analysis of 95 outer membrane proteins (OMPs) indicated significant antigenic variation, with 47 proteins exhibiting epitope loss and 11 displaying novel epitope gains. Beta-barrel structure prediction demonstrated a reduction in structural stability, with nine OMPs losing beta-barrel motifs, potentially influencing host-pathogen interactions. These findings highlight key genomic adaptations in BAS19 that may influence its immunogenic properties and vaccine efficacy. The results contribute to a deeper understanding of B. abortus genomic diversity, providing insights for the rational design of improved vaccines and therapeutics tailored to regional epidemiological needs.
Keywords: antigenic variation; bacterial virulence factors; Brucella abortus S19; comparative genomics; in silico analysis; SNP analysis; whole-genome sequencing; VIRULENCE; IDENTIFICATION; PROTECTION; PROTEIN; GENE; PREDICTION; EXSA; Veterinary Sciences